Clinical pathway as a strategy in improving healthcare quality and cost containment - Aniza I,; Saperi S,; Aljunid SM, (Penerbit UKM, 2008)
The increasing health care cost and public awareness on the delivery of high quality services has forced healthcare service providers to look into the healthcare delivery system. Clinical Pathway (CP) has been introduced in many hospitals and has been accepted as a beneficial tool in assisting healthcare organizations worldwide. Further, the CP also provides consistently high quality and coordinates services with minimum resources. It is proven to be a beneficial tool in other countries. CP is recently being introduced into the Malaysian healthcare system. The aim of this article was to high-light the benefits of CP in improving healthcare quality and controlling the medical cost. The relevant articles have been reviewed. The majority of literature reviewed con-cluded that there were positive effects in implementing CP. The CP was found to be significant in reducing length of stay and medical cost. The introduction of evidence based medicine, clinical outcomes, clinical audit, multidisciplinary communication, teamwork and care planning were also improved by CP. The challenges for healthcare providers and healthcare managers are to participate and be fully committed in path-way development and implementation in order to improve healthcare quality and cost control